2010
DOI: 10.1099/mic.0.033449-0
|View full text |Cite
|
Sign up to set email alerts
|

A 2-oxoacid dehydrogenase complex of Haloferax volcanii is essential for growth on isoleucine but not on other branched-chain amino acids

Abstract: The halophilic archaeon Haloferax volcanii contains three operons encoding 2-oxoacid dehydrogenase complexes (OADHCs) OADHC1-OADHC3. However, the biological role of these OADHCs is not known as previous studies have demonstrated that they cannot use any of the known OADHC substrates. Even the construction of single mutants in all three oadhc operons, reported recently, could not identify a substrate. Therefore, all three possible double mutants and a triple mutant were generated, and single, double and triple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, the DL1 genome was statistically overrepresented for COGs associated with BCAA uptake and catabolism, including OADHC components (Table 1, Supplementary Table S3). In archaea, certain OADHCs can catalyze the decarboxylation of branched-chain 2-oxoacids that result from BCAA catabolism, as well as pyruvate (Heath et al, 2004(Heath et al, , 2007Sisignano et al, 2010). Thus, these COGs associated with general amino acid metabolism, BCAA uptake and catabolism, and OADHC components, likely describe a common substrate preference by DL1.…”
Section: Dl1mentioning
confidence: 99%
“…In addition, the DL1 genome was statistically overrepresented for COGs associated with BCAA uptake and catabolism, including OADHC components (Table 1, Supplementary Table S3). In archaea, certain OADHCs can catalyze the decarboxylation of branched-chain 2-oxoacids that result from BCAA catabolism, as well as pyruvate (Heath et al, 2004(Heath et al, , 2007Sisignano et al, 2010). Thus, these COGs associated with general amino acid metabolism, BCAA uptake and catabolism, and OADHC components, likely describe a common substrate preference by DL1.…”
Section: Dl1mentioning
confidence: 99%
“…volcanii harbors three gene clusters that encode subunits of three 2-oxoacid dehydrogenase complexes, but the substrates and biological roles for all three enzyme complexes remained obscure for a long time [6772]. In an attempt to apply genetics to solve the question, seven strains were constructed that contained the three possible single gene deletions, the three possible double deletions, and a triple gene deletion [73]. Comparison of the extracellular metabolomes of wild-type and mutants revealed that the wild type depleted complex media of isoleucine, while mutants lacking one of the 2-oxoacid dehydrogenase complexes (OADHC-1) were unable to do so.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Comparison of the extracellular metabolomes of wild-type and mutants revealed that the wild type depleted complex media of isoleucine, while mutants lacking one of the 2-oxoacid dehydrogenase complexes (OADHC-1) were unable to do so. Subsequent analyses verified that OADHC-1 is indeed essential for degrading isoleucine but not the other branched-chain amino acids [73]. …”
Section: Metabolomicsmentioning
confidence: 99%
“…Hfx. volcan ii is also demonstrated to synthesize key metabolic enzymes that are TPP-dependent including the 2-oxoacid (α-ketoacid): ferredoxin oxidoreductases used to mediate the oxidative decarboxylation of pyruvate and 2-oxoglutarate [24] and three 2-oxoacid dehydrogenases used under nitrate-respirative conditions [25] including one involved in growth on isoleucine [26]. The ΔubaA mutant required to analyze the ThiS/ThiF-type pathway was already available from previous study [11].…”
Section: Resultsmentioning
confidence: 99%